Pengaruh Pengalaman Pelanggan dan Potongan Harga Terhadap Minat Beli Ulang Produk Luxcrime di Toko Kosmetik Panda Lovely Malang - Nafisa Irianto, Qinthara; Maskan, Mohammad; Utamaningsih, Arni (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Customer experience can increase the value of a product and influence the perspective of the company. In addition to customer experience, companies also need to consider promotional strategies, including providing discounts. This research was a quantitative research with variables of customer experience, discount and repurchase interest. The purposive sampling technique was used as a data collection technique through a questionnaire and as many as 100 people as respondents. Based on the research results, it can be concluded that customer experience and discounts are one of the reasons for repurchase interest. A positive and good customer experience will increase repurchase interest, besides the discount will attract customers to make repeat purchases.